Supersoft X-ray detections of M31 Novae with XMM-Newton - Henze, M.; Sasaki, M.; Haberl, F.; Hatzidimitriou, D. (2015)
We report the detection of three novae in recent XMM-Newton observations of the M31 disk (see also ATel #8227). Two 100-ks observations were carried out on 2015-06-28 (ObsID 0763120101; June) and 2015-08-11 (ObsID 0763120301; August) and have been analysed using the standard data reduction software.
Keywords: Nova; Transient